Where are you, Blue Kangaroo? - Chichester Clark, Emma. (New York : Dell Dragonfly Books, 2001)
After his best friend, Lily, accidentally leaves him alone in several strange places, Blue Kangaroo wonders if she will soon forget him altogether.
"First published in Great Britain in 2000 by Andersen Press"--T.p. verso.
"Read to a child"--Cover p. [4].
Booklist.
Bulletin (Center for Children's books).
School Library Journal.
2.7
Keywords: Kangaroos -- Fiction; Lost and found possessions -- Fiction; Stuffed animals (Toys) -- Fiction; Toys -- Fiction; Kangaroos -- Fiction; Lost and found possessions -- Fiction; Toys -- Fiction